Aesthetics and the philosophy of art : an introduction - Stecker, Robert, 1947- (Elements of philosophy., 2010)
Praised in its original edition for its up-to-date, rigorous presentation of current debates and for the clarity of its presentation, Robert Stecker's new edition of Aesthetics and the Philosophy of Art preserves the major themes and conclusions ofthe original, while expanding its content, providing new features, and enhancing accessibility. Stecker introduces students to the history and evolution of aesthetics, and also makes an important distinction between aesthetics and philosophy of art. Whileaesthetics is the study of value, philosophy of art deals with a much wider array of questions in.